Pengaruh Intellectual Capital Terhadap Profitabilitas Dalam Perspektif Syariah - Sandi Andika; Dewi Astini (JAS (Jurnal Akuntansi Syariah), 2022)
The stability of the company's operating system is an essential assessment of excellence in maintaining the company's economy. The success of a company can be seen from the profitability ratio. This research aims to show the effect of intellectual capital factors on profitability from a sharia perspective. This type of research is descriptive quantitative using panel data regression. The research population is manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. The sampling technique used purposive sampling in order to obtain 50 observational data. The results showed that value-added capital employed (VACA) negatively and significantly affected profitability. Value-added human capital (VAHU) and structural capital value added (STVA) positively and significantly affect profitability. Simultaneously intellectual capital has a significant effect on profitability. Activities and ways of managing companies related to intellectual capital and profitability follow sharia principles. This research can be used as a reference in evaluating aspects of intellectual capital in order to be able to make an optimal contribution to company performance following sharia principles.